2020
DOI: 10.18016/ksutarimdoga.v23i54846.722592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Heavy Metals on Germination and Seedling Growth of Sorghum

Abstract: Heavy metal contamination in soils can adversely affect seed germination and seedling growth of most plants. This research was conducted to determine the effects of different doses (0, 100, 200, 400 and 800 mg L-1) of Ni (nickel), Cd (cadmium), Pb (lead), Cr (chromium) and Hg (mercury) on seed germination and seedling growth of sorghum. The study was conducted in laboratory conditions at the Agricultural Faculty of Akdeniz University in 2017. Sorghum cv. N48×Early Sumac was used as the plant material. In the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This decline could be attributed to the high salt and heavy metal content in cement factory wastewater, which has been reported to negatively impact seed germination and seedling development. Ertekin et al [57] have also reported similar findings in sorghum irrigated with high amounts of heavy metal.…”
Section: Seedling Vigor Indexmentioning
confidence: 55%
“…This decline could be attributed to the high salt and heavy metal content in cement factory wastewater, which has been reported to negatively impact seed germination and seedling development. Ertekin et al [57] have also reported similar findings in sorghum irrigated with high amounts of heavy metal.…”
Section: Seedling Vigor Indexmentioning
confidence: 55%
“…Elevated concentrations of Ni can significantly impact cell division in root meristems, altering root length [40]. Similarly, a root length decrease due to the presence of Ni was also reported for Phacelia tanacetifolia, Cucumis sativus, and Brassica nigra [46]; Sorghum bicolor [47]; and Salsola vermiculata [48].…”
Section: Discussionmentioning
confidence: 80%